Water Quality Assessment and Risk Analysis Calculation of Chloride and Sodium Exposure of Well Water in Tanggulangin, Sidoarjo - Ilham Putra Adiyaksa; Akhmad Adi Sulianto; Savichev Oleg Gennadyevich (Universitas Brawijaya, 2022)
Tanggulangin is one of the areas affected by the Lapindo mud, also one of the sub-districts in Sidoarjo with many working industries. Some research reported that there was a decrease in the quality of well water in Tanggulangin due to these things, as well as a lack of public awareness of the environmental issues. Thus, this study aims to assess the quality of well water in the village of Kedensari, Tanggulangin, Sidoarjo based on physico-chemical characteristics. In addition, using the general equation from the EPA (Environmental Protection Agency), this paper discusses the calculation of the risk analysis of chloride and sodium exposure to health in three scenarios, 1) an adult weighing 80 kg and consuming water for 20 years; 2) an adult weighing 60 kg and consuming water for 20 years; and 3) children weighing 20 kg and consuming water for 8 years. Based on the measurement results of several parameters, physically and chemically, as well as organoleptic observations, and compared with the health ministry regulations, the water in the area is safe for consumption. However, based on the results of calculations, exposure to chloride and sodium from the water poses a risk to health in the specified time with an RQ value of more than 1. The risk from exposure to chloride is greater than from sodium.